Shear induced phase coarsening in Polystyrene/Styrene-ethylene-butylene-styrene blends - Wang, Yong; Wang, Cong; Zhang, Qin; Yang, Hong; Du, Rongni; Fu, Qiang (Journal of materials science, 2006)
The phase behavior of polymer blends under the effect of shear has been a subject of considerable interest from the viewpoint of both theoretical research and industrial application, because the shear stress is unavoidable during processing. In this work, we reported the change of phase behavior and mechanical properties of Polystyrene (PS)/Styrene-ethylene-butylene-styrene (SEBS) blends achieved via a shear-assistant injection molding, which was called dynamic packing injection molding (DPIM). The size of dispersed SEBS particles in PS matrix was found to be increased for the samples obtained by dynamic packing injection molding (DPIM), compared with those obtained by conventional molding, indicating a shear induced phase coarsening. The shear induced phase coarsening can be further demonstrated by the decrease of impact strength of dynamic packing injection molded samples. However, the shear-induced phase coarsening will be eliminated after annealing the samples at high temperature for certain time. The particle size, which related to the capability to deform under the effect of shear, was found to play an important role to determine the phase morphology. Our result suggested that shear stress induced phase coarsening was a process of not only molecular configuration change but also deformation change under shear.